Crossmatch, Donor-specific Antibody Testing, and Immunosuppression in Simultaneous Liver and Kidney Transplantation: A Review. Issue 12 (December 2021) - Das, Anushka; Taner, Timucin; Kim, Jim; Emamaullee, Juliet
Abstract : Since the introduction of simultaneous liver-kidney transplantation (SLKT) in the 1960s, the potential for immunological protection from the liver allograft to a simultaneously transplanted kidney has been recognized. Due to expanded indications and changes in allocation policies, there has been increased utilization of SLKT. Despite growing experience, a lack of consensus exists regarding the extent of the immunological privilege of the liver the role for donor-specific HLA antibody (DSA) and crossmatch testing, and appropriateness of modern immunosuppression protocols in SLKT recipients. This review provides a detailed analysis of SLKT outcomes in the context of these factors, suggesting that although the liver can reduce the incidence of antibody-mediated rejection, attention should be given to liver allograft function, previous failed transplants, and other risk factors in pretransplant risk assessment. Current methods of DSA and crossmatch testing in SLKT are also discussed, and the role of specific DSA (high mean fluorescence intensity antibody, C1q + binding) and their potential importance in posttransplant risk assessment are examined. Finally, trends in SLKT immunosuppression are discussed, including the use of nondepleting agents for induction and de-escalating use of steroids for maintenance immunosuppression. Ongoing research, including multicenter or randomized trials, will be necessary to optimize immune-related outcomes in SLKT recipients. Abstract : Supplemental Digital Content is available in the text.